"Pixadores de elite": duas décadas de uma grife - Flavia Cristina Soares (2013)
Wall spraying can be seen stamped on the walls of cities with phrases that express feelings or insurgency to a particular political regime and such messages are understandable to those who walk in a particular city. However, there is also wall spraying which does not convey any message or is unintelligible to the eye of the citizens. This kind of wall spraying means something only to members of a certain group of taggers which perform this practice. Entries made in the walls are signatures or nicknames created by taggers themselves and recognized as "detonas". Unintelligible wall spraying is a recent phenomenon and in the city of Belo Horizonte, it was originated in the 1980 decade. This research analyzes the dynamics of the relations between the members of a group of taggers in the metropolis of Belo Horizonte, called "Pixadores de Elite". Their story is unveiled with a field study carried out with this group. Some moments of interaction among members and their strolling around the capital of Minas Gerais are described and capital and mark the "detonas", the style of the letters and conflicts of taggers with police and government institutions.